Synergistic interactions between temporal coupling of complex light and magnetic pulses upon melanoma cell proliferation and planarian regeneration. (3rd April 2017) - Murugan, Nirosha J.; Karbowski, Lukasz M.; Persinger, Michael A.
ABSTRACT: Synergisms between a physiologically patterned magnetic field that is known to enhance planarian growth and suppress proliferation of malignant cells in culture and three light emitting diode (LED) generated visible wavelengths (blue, green, red) upon planarian regeneration and melanoma cell numbers were discerned. Five days of hourly exposures to either a physiologically patterned (2.5–5.0 μT) magnetic field, one of three wavelengths (3 kLux) or both treatments simultaneously indicated that red light (680 nm), blue light (470 nm) or the magnetic field significantly facilitated regeneration of planarian compared to sham field exposed planarian. Presentation of both light and magnetic field conditions enhanced the effect. Whereas the blue and red light diminished the growth of malignant (melanoma) cells, the effect was not as large as that produced by the magnetic field. Only the paired presentation of the blue light and magnetic field enhanced the suppression. On the other hand, the changes following green light (540 nm) exposure did not differ from the control condition and green light presented with the magnetic field eliminated its effects for both the planarian and melanoma cells. These results indicate specific colors affect positive adaptation that is similar to weak, physiologically patterned frequency modulated (8–24 Hz) magnetic fields and that the two forms of energy can synergistically summate or cancel.